La sobreprotección de los padres y su incidencia en el desarrollo de habilidades sociales, de los niños y niñas de educación inicial, nivel 1 del centro educativo bilingüe “Gotitas de Colores Gotael” de la ciudad de Quito, periodo lectivo 2013-2014”. Lineamientos alternativos - Salgado Poveda, Maximina Meybe (2014)
The present work investigative, called "THE PARENTS OVERPROTECTION AND THEIR INCIDENT IN LEVEL 1 INITIAL EDUCATIONAL CHILDREN SOCIAL SKILL DEVELOPMENT “GOTITAS DE COLORES GOTAEL” BILINGUAL EDUCATIONAL CENTER, QUITO CITY PERIOD 2013-2014 ".It has structured and developed of conformity to the Regulation of Academic Regime of Loja's National University. For the present investigation, the General objective was to determine the incident of the Parent’s Overprotection and their relation with Social Skill Development of the level 1 initial educational children. The used methods were scientific, Descriptive, Analytical - Synthetic, Inductive and Statistical Model. The techniques and instruments that were applied are the survey to the Family parents to establish the Overprotection of the children and, an observation guide to the children to evaluate the Development of Skills of the results of the survey there concludes that: 73 % of family parents polled demonstrates that they do not overprotect his children and 27 % they do it to protect the children is necessary but to overprotect is harmful, it can prevent, the creativity, the learning and the free development of the personality. 54 % of children the Level 1 of the "Gotitas de ColoresGotael" Infantile Center is located in the High Level of development of Social Skills, 27 % in the Average Level and 19 % in the Low level. The development of Social Skills it are a set of capacities that allow the development of actions and conducts that do that the children unroll effectively in the social thing. These skills are something complex since they are formed by a set of ideas, feelings, beliefs and values that are a fruit of the learning and of the practice. It is fundamental to pay particular attention to the development of the social skills, since first they are indispensable for the adjustment of the children to the environment in which they live and later these skills are going to provide the tools to them to be unrolled as adults in the society, being the key to survive in emotional and educational way